Chlorinated benzophenone derivatives as chemotaxonomic markers for the genus of Pestalotiopsis. (August 2020) - Lei, Hui; Niu, Hong; Song, Can; Fu, Xiujuan; Luo, Yu; Chen, Siwei; Zhang, Dan
Abstract: A chemical investigation of the extract of the marine-sponge-associated fungus P. colombiensis resulted in the isolation of eight chlorinated benzophenone derivatives, named, pestalone (1 ), pestalachlorides A-C, E, and F (2 -6 ), pestalalactone (7 ), and pestalalactone atropisomer (8 ). The structures of these compounds were identified by spectroscopic analysis (MS, 1D/2D NMR) and comparison with the previously reported data . Compounds (1 –8) were isolated from this species for the first time. Moreover, compounds (1 –8) had not been reported from any other genus, and the chemotaxonomic signifcance of eight chlorinated benzophenone derivatives (1 –8 ) was also discussed. Highlights: Chlorinated benzophenone derivatives (1-8 ) were isolated from the marine-sponge-associated fungus pestalotiopsis colombiensis. Compounds (1 –8) were isolated from this species for the first time. Chlorinated benzophenone derivatives (1 –8 ) could be used as chemotaxonomic markers for the genus of pestalotiopsis.